Enhancing learning through digital games in education - Batdi, Hacer; Doğan, Yunus; Saygin, Merve; Batdi, Veli (Nova Science Publishers Inc., 2025)
In the realm of education, the concepts of digitization and digital transformation have become pivotal, shaping new methodologies and relationships. Digitization in education not only defines the integration of digital technologies but also redefines how educators and learners interact with knowledge. This chapter explores various dimensions: from the classification of digital education models to the evolving roles of students and teachers within digital cultures. It emphasizes the criticality of 21st-century skills in navigating these digital landscapes, highlighting their integration into educational frameworks. Furthermore, the transition from traditional games to digital platforms reflects broader societal shifts, underscoring the concept's historical evolution and its impact on educational paradigms. The application of gamification in education emerges as a strategic tool, elucidating its implementation strategies and the resultant benefits for learners. Moreover, the use of digital games in education elucidates its associated concepts and the evolving dynamics of their roles within educational settings. This chapter synthesizes a comprehensive understanding of digitization's impact on education, addressing both theoretical underpinnings and practical implications, thereby paving the way for future advancements in educational practices and policies. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Digital game-based learning, 21st century skills; Digital games